Spatial Diversity of Macrobenthic in Ngenep Spring Due to Anthropogenic Activities - Wiratno, Ekwan Nofa; Nurdiansyah, Rizky; Basyaruddin, M.; Riyanto, Slamet; Rupilu, Novie S.; Retnaningdyah, Catur (Journal of Indonesian Tourism and Development Studies, 2016)
This aims of this study are to determine the macrobenthic community structure between the drainage near residence and spring; and to determine effect of local environment on macrobenthic community structure at the Ngenep village. Field study was conducted in 3 drainage, i.e. residential drainage, spring and rice field irrigation. Macrobenthic were sampled by the surber net and hand net in three stations in each drainages. Abiotic factors were assessed at the same stations. Macrobenthic community structure and diversity was determined using Important value index, Shannon-Wiener index and Bray Curtis index. Cluster of benthics and abiotic factors were analysis using Principal Component Analysis (PCA). Abiotic data showed no statistical significance in 3 drainage (P>0.05) but showed increasing trend from spring to field irrigation and the highest at residential drainage. The 17 taxa of macrobenthic were found with high important value index are Melanoides tuberculata, larva's of Ephemeroptera and Plecoptera. Highest Shannon-Wiener index observed at irrigation (2.781). The cluster analysis of abiotic factor showed that spring was in different cluster with residential and irrigation, meanwhile, PCA analysis of macrobenthic showed each place was different cluster. Conclusion of this study is anthropogenic activities alter the diversity and community structure of macrobenthic. Keywords: Anthropogenic Activity, Macrobenthic, Ngenep.